PENGARUH PROFITABILITAS TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Nicolas Ernesto; Hisar Pangaribuan (Jurnal Ekonomis, 2021)
The aim of this study is to find out how profitability effect Corporate Social Responsibility (CSR) with the target study is 40 banks in Indonesia during 2018-2019. Profitability is “as an independent variable and Corporate Social Responsibility as dependent variable in the current research. The study is purposive sampling technique. The data used in this study is secondary data taken from www.idx.co.id. This research uses multiple linear regression analysis model. This study obtains results that prove that Net Profit Margin and Earning Per Share have no significant effect on Corporate Social Responsibility Disclosure. The analysis of the coefficient of determination shows the results of the adjusted R square value in the coefficient of determination test of 1.2%, where the remaining 98.8% is influenced by other variables. This shows that the independent variables in this study are not sufficiently influential on CSR disclosure because there are still many other variables that have a major influence on CSR disclosure.